Amalgamasi Sunni dan Syi’ah di Kampung Arab Bondowoso - Musdhalifah Musdhalifah (Islamika Inside: Jurnal Keislaman dan Humaniora, 2019)
Abstract: Marriage aims to achieve the happiness of family members. The phenomenon of inter-sectional marriage between Sunnis and Shiites 60% occurin the Bondowoso Arabian Community. Although between the two sects there are differences in Sunni and Shia teachings which can be said to be very much different. One of them is a matter of perspective from aqidah but they can undergo differences in the family. If in the difference disputes and tensions occur in the family so the marriage is not done. The Indonesian Ulema Council (MUI) Bondowoso has a different opinion from the response of the Central Indonesian Ulama Council (MUI) to the Shiite groups in Bondowoso on the grounds so that the people in Bondowoso are safe and secure. Concerned that the Bondowoso community is in conflict between two groups.